Evolution of the Lower Valley of Oued Za during the Quaternary (Northeastern Morocco) - BENHAMED, Abderrahim; SBAI, Abdelkader (Journal of natural sciences, life and applied sciences, 2025)
Oued Za, upon exiting the Jerada mountain range, flows from the southeast to the northwest and joins the Moulouya River. Its valley contains abundant Plio-Quaternary alluvial formations. Surveys conducted using a Leica GPS station allowed the production of accurate transverse geological cross-sections and a distribution map of Quaternary formations at a 1:50,000 scale. The lithological, stratigraphic, and morphological data show that, since the end of the Pliocene, episodes of alluvial deposition and erosion have alternated, primarily driven by climatic fluctuations. These various formations are the result of pluvial periods. The erosional episodes, which brought out the glacis, as well as the middle and lower terraces and calcareous crusts, are linked to dry periods. Finally, lithological and chronostratigraphic correlation was established among the different formations to produce a schematic stratigraphic cross-section.